Amazon Redshift: The Definitive Guide : jump-start analytics using cloud data warehousing - Francis, Rajesh; Gupta, Rajiv (Manager of analytics); Oke, Milind (Sebastopol, CA : O'Reilly Media, 2023)
"Amazon Redshift powers analytic cloud data warehouses worldwide, from startups to some of the largest enterprise data warehouses available today. This practical guide thoroughly examines this managed service and demonstrates how you can use it to extract value from your data immediately, rather than go through the heavy lifting required to run a typical data warehouse."--Amazon.com.
AWS for data -- Getting started with Amazon Redshift -- Setting up your data models and ingesting data -- Data transformation strategies -- Scaling and performance optimizations -- Amazon Redshift machine learning -- Collaboration with data sharing -- Securing and governing data -- Migrating to Amazon Redshift -- Monitoring and administration.
Includes index.
Revised history for the first edition.
Keywords: Amazon Web Services (Firm); Data warehousing; Web services